2011
DOI: 10.1158/1940-6207.capr-10-0117
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Efficacy and Mechanism of Licofelone in a Mouse Lung Tumor Model via Aspiration

Abstract: Our previous study comparing inhalation and aspiration to administer agents directly to lung indicated that aspiration route is as effective as inhalation while reducing costs for equipment and chemopreventive agent. This study evaluated the chemopreventive efficacy and mechanism of Licofelone, a dual inhibitor of cyclooxygenase-2 (Cox-2) and 5-lipoxygenase (5-Lox), via oropharyngeal aspiration against mouse lung adenoma. Eight week old female A/J mice were given three doses of benzo[a]pyrene (B[a]P, 2 mg/dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…A dose-dependent inhibition of PCNA expression with an increase in apoptosis also was observed in licofelone-treated lung tumors (16) as well as colon tumors (15, 37). Similarly, dose-dependent inhibition of COX-2 and 5-LOX was observed with licofelone treatment in lung tumors (16). We found that licofelone had a modulatory effect on cell-cycle regulatory proteins like Cyclin E and p16.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A dose-dependent inhibition of PCNA expression with an increase in apoptosis also was observed in licofelone-treated lung tumors (16) as well as colon tumors (15, 37). Similarly, dose-dependent inhibition of COX-2 and 5-LOX was observed with licofelone treatment in lung tumors (16). We found that licofelone had a modulatory effect on cell-cycle regulatory proteins like Cyclin E and p16.…”
Section: Discussionmentioning
confidence: 70%
“…Licofelone inhibited colonic tumors in a mouse colon cancer model by 72-100%, caused a significant reduction in small intestinal polyps (15), and provided better efficacy that did celecoxib in suppressing tumor growth. In a benzo( a )pyrene-induced lung cancer model, licofelone inhibited tumor multiplicity by 26% with a significant decrease in tumor incidence (16). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were infected with adeno-Cre and transferred to a tamoxifen-containing diet, as in the earlier experiments. Two weeks following the addition of tamoxifen, mice were treated with either vehicle or licofelone-a dual COX/5-LOX pathway inhibitor, which has shown promising chemopreventive efficacy in lung and colon cancers (34,35). Remarkably, after only four doses we found substantially reduced tumor load when compared with vehicletreated controls (Fig.…”
Section: In Vivo Inhibition Of Cox/5-lox Pathways Reduces Proliferatimentioning
confidence: 79%
“…To date, several NSAIDs with dual COX-2/5-LO activity have undergone clinical testing for use in the treatment of inflammatory diseases, with licofelone (2-[2-(4-chlorophenyl)-6,6-dimethyl-1-phenyl-5,7-dihydropyrrolizin-3-yl]acetic acid) being the most advanced. In addition to demonstrating an excellent tolerability, licofelone has been shown to have a dose-dependent anticancer effect in cell culture and in animal models (2022). So far studies have focused on the ability of licofelone to directly inhibit PG (21) and LT synthesis (23) and induce apoptosis in tumor cells; however, little is known about its direct effects on immune cell populations in the context of cancer.…”
Section: Introductionmentioning
confidence: 99%